Perceived barriers and effectiveness of ART services among people living with HIV and AIDS under treatment. - Silwal, Shankar (2014)
ABSTRACT: This study was conducted at Sukraraj Tropical and Infectious Disease Hospital, Teku Kathmandu in order to identify the perceived barriers and effectiveness of ART services among 261 people living with HIV and AIDS and receiving ART services from the Hospital. The required data were collected from purposively selected 261 respondents through interview using interview schedule. Additional data were collected from hospital records of 195 respondents. This study found that male population is higher (57.9 %) than Female (42.1 %) population. Female illiteracy rate is higher than male. Age between 19 to above 70 years old persons have acquired the disease. Ten percent of people was widow, had been missed their family due to HIV and AIDS. Fifty two out of 261 people didn't hear about HIV and AIDS before acquired the disease. Furthermore, 99 male and 45 female populations were acquired by unprotected sexual contact. Sero-discordance transmission of respondents were 71 and 63 only female were acquired HIV by sero-discordance. 47.7% people didn't not get a test on time due to including perception of good health however 20.3 percent of people had not got a test due to fear of disclosure of the HIV status. Meanwhile 36.1% people were worried on social stigma during test. 57.7% of respondents have been staying in outside Kathmandu. A Central ART clinic is situated in Teku, Kathmandu. Similarly, 52.1 percent of population has faced to fearing on disclose to other and 23 % of study respondents were not accepted and not allow in social activities. In addition, 41.8 percentage expressed that vulnerable person are not come to check up on time due to fearing of disclosure of their virus status. 65.1 percent of respondents have been getting the progression of Health status after ARV. 40.6 percent of population had stable in normal range CD4 count after taking ART services through hospital. 46.4 % had not faced any co-infections after taking ARV. A large majority of respondents i.e. 66.3 % did not support to get a test for his/her spouse /or partner. 47.5 percent respondents said that better to provide newly medicines which are less harm rather than we have now. Among of them 42.5 percent of respondents didn't like home base services because of fearing to disclose with other and society.